Preparation of an anti‐isoprocarb monoclonal antibody and its application in developing an immunochromatographic strip assay. (27th August 2019) - Zhang, Xiaoping; Liu, Liqiang; Cui, Gang; Song, Shanshan; Kuang, Hua; Xu, Chuanlai
Abstract: In this study, a carboxyl group was introduced into the isoprocarb molecule to obtain an isoprocarb hapten, which was then coupled with a protein to obtain an artificial antigen. Three monoclonal antibody cell lines, 1D11, 6E6 and 1B5, were finally obtained by mouse immunization, cell fusion and subcloning, and the antibody produced by cell line 1B5 had the best affinity and sensitivity. The monoclonal antibody was highly sensitive and specific for isoprocarb, with an IC50 of 2.09 ng/ml and a cross‐reactivity rate of <0.21%. By optimizing the indirect competitive (ic)‐ELISA, the optimal conditions were determined to be pH 7.4, 0% methanol and 0.8% NaCl, the limit of detection value was 0.23 ng/ml, and the linear range of the ic‐ELISA was 0.46–9.62 ng/ml. The recovery rate of the isoprocarb cucumber sample was 97–99% for the ic‐ELISA method. In addition, we successfully developed an immunochromatographic test strip for the detection of isoprocarb residues. The cutoff values in phosphate‐buffered saline and cucumber extract were 10 and 25 ng/ml, respectively. Both methods met the requirements for isoprocarb residue detection in agricultural products, and can be used for semiquantitative and qualitative analysis of isoprocarb in vegetables.